Gas Emissions From the Western Aleutians Volcanic Arc - Fischer, Tobias P.; Lopez, Taryn M.; Aiuppa, Alessandro; Rizzo, Andrea L.; Ilanko, Tehnuka; Kelley, Katherine A.; Cottrell, Elizabeth (Frontiers in Earth Science, 2021)
The Aleutian arc is remote and highly active volcanically. Its 4000 km extent from mainland Alaska to Russia’s Kamchatka peninsula hosts over 140 volcanic centers of which about 50 have erupted in historic times. We present data of volcanic gas samples and gas emission measurements obtained during an expedition to the western-most segment of the arc in September 2015. Some of the volcanoes investigated here have not been sampled for gases before this writing. Our data show that all volcanoes host high-temperature magmatic-hydrothermal systems and have gas discharges typical of volcanoes in oceanic arcs. Based on helium isotopes, the western Aleutian arc segment has minimal volatile contributions from the overriding crust. Volcanic CO2 fluxes from this arc segment are small, compared to the emissions from volcanoes on the Alaskan Peninsula and mainland Alaska. The comparatively low CO2 emissions may be related to the lower sediment flux delivered to the trench in this part of the arc.